PENGGUNAAN METODE BELAJAR BERBASIS GAME SEBAGAI UPAYA MEMECAHKAN PROBLEMATIKA DALAM PEMBELAJARAN SEJARAH - Ananda Savira Vinidiansyah; Nurhaniah Nurhaniah; Andi Andi (Universitas Negeri Malang, 2021)
This study aims to find out about the implemention of game-based learning methods that can be used by history teachers to create better and interesting learning activities, this is because many teachers are less skilled in using learning methods. In fact, if you look closely, there are various kinds of learning methods that can be used to lure students to be more active in creating a pleasant learning atmosphere, especially in history learning, such as the use of game-based learning methods. The method used in this study is a research method with a descriptive qualitative approach. The data sources used in this study are classified into two sources, namely primary data sources and secondary data sources. Primary data sources were obtained through interviews with informants, namely five students who had experience learning game-based history at the X, XI, and XII grades of SMAIT Mentari Ilmu Karawang, SMAI Al-Azhar Summarecon Bekasi, SMAN 13 Tangerang, SMAN 1 Teluk Jambe Timur, and SMAIT Al-Irsyad Karawang. Meanwhile, secondary data sources are obtained through documents in the form of books, scientific journals or studies that are relevant to the research theme. The results of this study indicate that from various schools, teachers in carrying out learning, especially in history subjects, have used game-based learning methods. Game-based learning used by teachers are games such as Kahoot, Quizizz, WorldWall, QuizWhizzer, Educandy and some even play guessing pictures. The game can be used easily without taking a long time. Learning history by using games can make the learning atmosphere more exciting and challenging. So game-based learning can be used by teachers to avoid monotonous and boring activities. With this game-based learning, especially in history lessons, it can change the public's view of the image of history which was previously considered to be of the view that learning history is not too exciting.